Social-psychological aspects of intergroup conflict and reconciliation in Northern Ireland: the role of trust and forgiveness - Myers, E (2007)
This thesis aimed to investigate the concepts of trust and forgiveness, in the context of post-conflict reconciliation in Northern Ireland. Chapter 1 gives an overview of the historical background of the conflict in Northern Ireland, the current situation in terms of the divided relationship between the Catholic and Protestant communities and argues that reconciliation initiatives need to encompass social, psychological and emotional aspects of the conflict. Chapter 2 outlines the theoretical framework for the empirical research in the following chapters. Social-psychological theories of conflict are discussed, with particular emphasis on the social identity perspective. These theories are then applied to the conflict, intergroup relations and reconciliation in Northern Ireland. The concepts of trust and forgiveness are defined and conceptualised from this theoretical background.